2004
DOI: 10.1016/s0889-5406(03)00507-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloy type and surface conditioning on roughness and bond strength of metal brackets

Abstract: The effect of 5 different surface conditioning methods on bonding of metal brackets to cast dental alloys was examined. The surface conditioning methods were fine (30-microm) or rough (125-microm) diamond bur, sandblasting (50-microm or 110-microm aluminum oxide [Al2O3]), and silica coating (30-microm silica). Fifty disc-shaped specimens of 5 different alloys (gold-silver, palladium-silver, nickel-chromium, cobalt-chromium, and titanium) were ground with 1200-grit silicone carbide abrasive and polished before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…In addition, energy-dispersive X-ray analysis revealed that a high alumina (26.0 wt%) content remained on the titanium surface after alumina abrasion and that the SiO 2 content on the titanium surface was 13.7 wt% after ROC tribochemical silica coating 21) . According to a previous study, the surface roughness of titanium after 110-μm particle alumina abrasion was larger than that after 50-μm particle alumina abrasion 24) . Although the particle size for ROC-a is larger (110-μm) than that for SAN (50-70-μm), in the present study, the Rz values did not differ significantly between ROC-a and SAN (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, energy-dispersive X-ray analysis revealed that a high alumina (26.0 wt%) content remained on the titanium surface after alumina abrasion and that the SiO 2 content on the titanium surface was 13.7 wt% after ROC tribochemical silica coating 21) . According to a previous study, the surface roughness of titanium after 110-μm particle alumina abrasion was larger than that after 50-μm particle alumina abrasion 24) . Although the particle size for ROC-a is larger (110-μm) than that for SAN (50-70-μm), in the present study, the Rz values did not differ significantly between ROC-a and SAN (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…Half of the specimens from each group were randomly (n=10 per group) selected and subjected to thermocycling (Nova, Nova Co, Konya, Turkey) for 1000 cycles [9], between 5-55°C, with a transfer time of 30 s and a dwell time of 30 s [16]. After thermocycling, the specimens were loaded at the bracket-specimen interface at a crosshead speed of 0.5 mm/min in a Universal Testing Machine (Lloyd Instruments, Hampshire, UK) until failure.…”
Section: Aging and Bond Strength Testmentioning
confidence: 99%
“…Although shear bond strength of metal orthodontic brackets to amalgam, methacrylate-based resin composites and dental ceramics have been widely investigated [14][15][16][17], their adhesion to IRCs have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more orthodontists are using direct bonding to metal restorations because of improved oral hygiene, as well as convenience to the practitioner, compared with the conventional method using bands. Recently, chemicophysical bonding using a silica coating and silanation (silicoating),7,8 which can enhance mechanical and chemical bonds, has been introduced in the field of orthodontics. Chemically cured resin is more fully polymerized than light-cured resin, particularly in the central area of the bracket, when a metal bracket is bonded to gold alloy 9.…”
Section: Introductionmentioning
confidence: 99%